Caregivers’ perceptions and expectations regarding the Home-based Care Program of the Pablo Neruda Family Health Center in Lo Prado. Chile, 2013. - Juanillo, Hugo; Sulbrandt, José (Revista Chilena de Salud Pública, 2019)
Introduction. The home-based care program for users with severe dependence, established in the Chilean public health system in 2006, provides services to individuals who are affected by a disability and who have a caregiver. These caregivers play a key role in communicating the healthcare needs of the users to their corresponding primary care centers, known as Family Health Centers (CESFAM) in Chile. In this context, this study seeks to explore caregivers’ perceptions and expectations regarding the health care administered to users in their homes. Objective. To explore the perceptions and expectations of caregivers about the healthcare offered by the Home-based Care Program of the Pablo Neruda CESFAM in Lo Prado, Chile. Methods. A qualitative approach inspired by the phenomenological tradition was used to study the social context of 11 caregivers. In-depth interviews were conducted to collect data through intentional sampling. The analysis was guided by Moustakas’ proposed methodology. Results. The caregivers’ main perceptions regarding the program were related to the economic and technical support offered in their homes, while their expectations focused on increasingqualified human resources and improving the economic aid that is granted. Conclusion. Thereis an urgent need for a more pronounced role of the State in strengthening the available support networks for caregivers. Additionally, steps should be taken to consider increasing financial aid for this vulnerable group, given the high burden of out-of-pocket healthcare payment.